2004
DOI: 10.1093/jn/134.5.1081
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of a Diet Low in Carotenoids with Tomato or Carrot Juice Does Not Affect Lipid Peroxidation in Plasma and Feces of Healthy Men

Abstract: Antioxidant properties of carotenoids are thought to be at least partly responsible for the protective effects of fruits and vegetables rich in carotenoids against colon cancer. There are large amounts of in vitro data supporting this hypothesis. But there is little known about the antioxidant effects of carotenoid-rich food in vivo particularly in the gastrointestinal tract. In a randomized, crossover trial, healthy men (n = 22) who were consuming a low-carotenoid diet drank 330 mL/d tomato juice or carrot ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 13 publications
3
39
3
3
Order By: Relevance
“…Rao and Shen (2002) also reported a significant decrease in serum lipid peroxidation and protein oxidation in healthy volunteers, following a 2-week consumption of tomato ketchup or oleoresin capsules, with baseline serum lycopene levels less than 0.2 mmol/l. These baseline plasma lycopene levels were lower than those reported by Riso et al (1999), Briviba et al (2004) and Hininger et al (2001) in their studies (0.34, 0.2 and 0.63 mmol/l, respectively). Thus, there may be a possibility that a depleted baseline lycopene level shows a better response to tomato antioxidant supplementation, than subjects with higher values.…”
Section: Mechanisms Of Action Of Lycopenecontrasting
confidence: 75%
See 1 more Smart Citation
“…Rao and Shen (2002) also reported a significant decrease in serum lipid peroxidation and protein oxidation in healthy volunteers, following a 2-week consumption of tomato ketchup or oleoresin capsules, with baseline serum lycopene levels less than 0.2 mmol/l. These baseline plasma lycopene levels were lower than those reported by Riso et al (1999), Briviba et al (2004) and Hininger et al (2001) in their studies (0.34, 0.2 and 0.63 mmol/l, respectively). Thus, there may be a possibility that a depleted baseline lycopene level shows a better response to tomato antioxidant supplementation, than subjects with higher values.…”
Section: Mechanisms Of Action Of Lycopenecontrasting
confidence: 75%
“…Riso et al (2004) observed no effects on lymphocyte resistance from lipid oxidation, following a 3-week supplementation of tomato products (8 mg lycopene/ day). Briviba et al (2004) also reported null effects on lipid peroxidation in plasma and feces in healthy men following a 2-week supplementation of 330 ml/day of tomato juice. Hininger et al (2001) further supplemented healthy male volunteers with 15 mg of natural tomato lycopene extracts for 12 weeks, and reported no effects on LDL oxidizability.…”
Section: Mechanisms Of Action Of Lycopenementioning
confidence: 96%
“…-Carotene is proposed to be efficient scavenger of singlet oxygen and it attenuates oxidative stress, however it does not directly inhibit lipid peroxidation (Briviba et al, 2004).…”
Section: Benefits Of Antioxidants Against Lipid Peroxidationmentioning
confidence: 99%
“…Toutefois, la plupart des études in vivo [14,18,23,24,29,30,33,53] montrent que la consommation en fruits et légumes chez des sujets en bonne santé n'entraîne pas de façon significative une diminution des dommages oxydatifs au niveau des lipides ou de l'ADN. Ces résultats sont évidemment décevants puisque cela est en contradiction avec le fait que la concentration plasmatique en antioxydants est augmentée après un apport interventionnel en fruits et légumes.…”
Section: Influence De La Consommation De Fruits Et Légumes Sur Les Maunclassified